Developing high frequency trading systems : learn how to implement high-frequency trading from scratch with C++ or Java basics /: learn how to implement high-frequency trading from scratch with C++ or Java basics. (2022) - Donadio, Sebastien; Ghosh, Sourav; Rizzo, John; Rossier, Romain
No abstract available